2013
DOI: 10.2224/sbp.2013.41.5.751
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis of the Regulatory Emotional Self-efficacy Scale of Chinese College Students

Abstract: In this study we assessed the regulatory emotional self-efficacy (RESE) of Chinese college students by collecting documentary resources and consulting relevant scales. The participants in the study were 927 college students from the provinces of Jiangsu, Guangdong, Anhui, and Gansu. Exploratory factor analysis and confirmatory factor analysis were both applied in the scale analysis. The RESE scale of Chinese college students consisted of perceived self-efficacy in managing inferiority, happiness or contentment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…It is crucial to examine the structure of the scale in Turkish language. As a result of the confirmatory factor analysis, it was determined that the RESE maintained its original structure in Turkish which is determined in Italy, Bolivia, USA (Caprara et al, 2008) and China (Zhao et al, 2013). Receiving a similar result in Turkish culture in which this study was conducted showed consistency with the previous study.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…It is crucial to examine the structure of the scale in Turkish language. As a result of the confirmatory factor analysis, it was determined that the RESE maintained its original structure in Turkish which is determined in Italy, Bolivia, USA (Caprara et al, 2008) and China (Zhao et al, 2013). Receiving a similar result in Turkish culture in which this study was conducted showed consistency with the previous study.…”
Section: Discussionsupporting
confidence: 82%
“…This is a significant finding suggesting that the RESE is a global scale. Also, it was concluded that the consistency level of the scale in Turkish is satisfactory for total; measuring the concept of emotional self-efficacy while especially for different factor structures obtained in China (Zhao et al, 2013), regulatory emotional self-efficacy had different qualifications in Chinese culture.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…10, No. 1; 2017 emotional situation, and to understand the feelings of others, and to identify positive and negative emotional expressions with a level of self-confidence of an ability to adapt to emotional effectively situation and adapt to the surrounding events, and the ability perceived as avoiding anger and frustration and negative emotions and face success and positive events and the expression of positive emotions in an appropriate manner (Zhao et al, 2013). And it is an individual's judgment on his ability to identify and understand self-emotions and manage those emotions, and dealing with the emotions that emerge from the others, and the ability to perceive emotion through facial expressions and body language, which is calculated by the degree which the faculty member obtain on emotional self-efficacy scale used for the purposes of this study.…”
Section: Definition Of Termsmentioning
confidence: 99%